Use of Biomaterials for 3D Printing by Fused Deposition Modeling Technique: A Review - Wasti, Sanjita; Adhikari, Sushil (Frontiers in Chemistry, 2020)
Three-dimensional (3D) printing is a revolutionary manufacturing technique that can fabricate a 3D object by depositing materials layer by layer. Different materials such as metals, polymers, and concretes are generally used for 3D printing. In order to make 3D printing sustainable, researchers are working on the use of different bioderived materials for 3D printing. Because of the abundant and sustainable sources, and versatile properties, biomaterials are considered as the potential candidates that have the ability to replace petroleum-based polymers. This review highlights the basic overview of fused deposition modeling (FDM) technique of 3D printing and recent developments that have occurred on FDM printing using biomaterials. Specifically, FDM printing process, final properties, and characteristics of biopolymers, their composites, and polymers containing biofillers are discussed.